Peran Sistem Informasi Industri Nasional (SIINas) dalam Mendukung Pelaporan Data Industri Berbasis Digital di Indonesia - Safira, Olivia; Zulkhairatullail, Zulkhairatullail; Kumbara, Vicky Brama (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the strategic role of SIINas in supporting industrial data reporting, particularly following the implementation of quarterly reporting obligations as stipulated in Minister of Industry Regulation Number 13 of 2025. This research employs a descriptive qualitative approach using a literature review method. The data sources consist of official documents issued by the Ministry of Industry, including Ministerial Regulation Number 13 of 2025, SIINas account registration guidelines, and technical guidelines for quarterly production reporting. Data were collected through systematic document review, careful reading, and identification of information relevant to the research objectives. The data analysis process involved data reduction, descriptive presentation, and interpretation to draw conclusions based on the examined regulatory and technical documents. The findings indicate that SIINas plays a significant role in improving data standardization, accuracy, and integration within the national industrial sector. The system enhances data consistency and sustainability while promoting transparency and accountability in industrial reporting. Therefore, SIINas functions not only as an administrative reporting tool but also as a strategic information system supporting evidence-based industrial policy in Indonesia.